2021
DOI: 10.1186/s43055-020-00403-y
|View full text |Cite|
|
Sign up to set email alerts
|

The role of 18-FDG PET/CT assessment of functional brain metabolism in cancer patients after chemotherapy

Abstract: Background Most neuropsychological studies on chemotherapy (CHT)-treated cancer survivors reported cognitive impairments in multiple domains such as executive functions, learning, memory, attention, verbal fluency, and speed of information processing. The CHT effects range from small to moderate, involving mostly the cognitive functions sub-served by frontal lobe. This study aimed to evaluate the role of PET/CT in the assessment of the effect of chemotherapy on the glucose metabolism in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Postchemotherapy FDG PET studies of the brain after treatment for various other cancers have also shown effects in these regions, with the frontal and temporal lobes most consistently affected across various cancers. [25][26][27][28][29] Thus, as one of the larger FDG PET studies in this arena, our study contributes to, validates, and corroborates the small but growing body of literature showing that the frontal and temporal lobes may be particularly vulnerable to cancer therapy. One limitation of our use of SPM default relative threshold masking is that some periventricular white matter is excluded from analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Postchemotherapy FDG PET studies of the brain after treatment for various other cancers have also shown effects in these regions, with the frontal and temporal lobes most consistently affected across various cancers. [25][26][27][28][29] Thus, as one of the larger FDG PET studies in this arena, our study contributes to, validates, and corroborates the small but growing body of literature showing that the frontal and temporal lobes may be particularly vulnerable to cancer therapy. One limitation of our use of SPM default relative threshold masking is that some periventricular white matter is excluded from analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Our study did have some limitations, other confounding variables were not considered such as effects of interval chemotherapy; studies have shown a significant reduction in brain metabolism after chemotherapy, which in turn decreases normal FDG uptake within the brain [23]; however, the most affected regions were found to be the mesial temporal lobes as well as the frontal lobes, neither region were used in our study to draw ROIs [24]. The number of patients in each response group was not equal, with predominance of regression group, metabolic flare phenomenon which is a potential pitfall in progression group were not evaluated, there was predominance of certain malignancies such as lymphoma, breast, lung over others such as pancreatic and gastric.…”
Section: Discussionmentioning
confidence: 99%
“…In daily practice, the selection bias is the rule as the doctor is searching for cases and a 29/32 (90%) efficiency is hence very surprising. 18FDG PET-CT allows brain metabolism to be directly assessed [59]. In a recent study by Verger et al, 47% of the scans of 143 patients with suspected neurological PACS were visually interpreted as abnormal [51].…”
Section: Clinical Approachmentioning
confidence: 99%